2016
DOI: 10.1039/c6dt00612d
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different coordination environments on one-dimensional Cu(ii) coordination polymers for the photo-degradation of organic dyes

Abstract: Three new Cu(ii) coordination polymers, namely, {[Cu3(L(1))(NO3)2(DMF)(H2O)]·3(DMF)}n (), [Cu3(L(1))(Cl)2(DMF)2]n () and [Cu3(L(2))(NO3)4(H2O)4]n (), were synthesized from pyridine-2,6-dicarbohydrazide based imine linked tritopic ligands. All the complexes were characterized using elemental analysis, IR, UV-vis spectroscopy and ESI-MS. The solid state structures of complexes were determined using single crystal X-ray crystallography. The complexes contain trinuclear copper units connected through different ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 70 publications
1
25
0
1
Order By: Relevance
“…The •OH generated on light irradiation might oxidize MB, ultimately resulting in the degradation of dye. In order to determine the active species generated during the photocatalytic process, experiments were carried out using isopropyl alcohol (IPA), ammonium oxalate (AO), benzoquinone (BQ), that act as scavenger towards •OH, H + and •O 2 − species, respectively . The degradation efficiency of MB by CP2 was greatly inhibited by the presence of IPA, while the effect of AO and BQ is lower.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The •OH generated on light irradiation might oxidize MB, ultimately resulting in the degradation of dye. In order to determine the active species generated during the photocatalytic process, experiments were carried out using isopropyl alcohol (IPA), ammonium oxalate (AO), benzoquinone (BQ), that act as scavenger towards •OH, H + and •O 2 − species, respectively . The degradation efficiency of MB by CP2 was greatly inhibited by the presence of IPA, while the effect of AO and BQ is lower.…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the active species generated during the photocatalytic process, experiments were carried out using isopropyl alcohol (IPA), ammonium oxalate (AO), benzoquinone (BQ), that act as scavenger towards * OH, H + and * O 2 À species, respectively. [41][42][43][44] The degradation efficiency of MB by CP2 was greatly inhibited by the presence of IPA, while the effect of AO and BQ is lower. Therefore, it may be concluded that the * OH is the species mainly responsible for photocatalytic degradation of dye ( Figure 12).…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…Unless otherwise specied, chemicals were purchased from commercial suppliers and used without further purication. 16 The NMR spectra of the ligands were performed in DMSO-d 6 with TMS as an internal reference, on JNM-ECS400 (JEOL) instrument operating at 400 MHz for 1 H NMR. were purchased from Aldrich.…”
Section: Materials and Measurementsmentioning
confidence: 99%
“…Recently we have reported nickel(II) complexes of some Schiff bases and found them to exhibit reasonable phosphatase like and photocatalytic activities. 16 The nally synthesized products were identied by their reported physicochemical properties. The hetero-catalytic activities of these complexes, towards phosphate ester bond cleavage were studied and structure activity relationship of these complexes with appropriate mechanisms is nally reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, degradation of organic pollutants assisted only by solar energy as a clean renewable source has received considerable interest. In this respect, different types of photocatalysts have been devoted for this aim including plasmonic metals-based materials, [1][2][3][4] metal-organic frameworks (MOFs), 5-10 organic polymers based compounds, 11,12 graphene and carbon nitride-based materials, [13][14][15] metal complexes, 16,17 hybrid compounds, and composites. [18][19][20] Among them, metal oxides such as TiO 2 , WO 3 , CeO 2 , Cu 2 O and ZnO have been extensively used as photocatalysts for such application type.…”
Section: Introductionmentioning
confidence: 99%